PENGARUH STUDENT TEAMS-ACHIVEMENT DIVISIONS TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK KELAS IV - Nabilah, Hariani Nisa; Margiati, K.Y; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to investigate the effect of students teams-achievement divisions on the students' learning achievement in the thematic lesson to Year-4 students of Elementry School 03 Pontianak Selatan. The researcher conducted the Pre-Experimental Research with pre-test and post-test one group design. The population of this research was all of Year-4 students of Elementry School 03 Pontianak Selatan, and the researcher took the sample by using stratified sampling, based on the students school report card in Academic Year 2017/2018. The sample of this research consist of 34 students in class IV A. The researcher collected the data by using the measurement technique in a multiple choice form. According to the research findings, pre-test (62.74) and post-test (73.56), tcount (7.317) and ttable (α = 0.05 and dk = 34 - 1 = 33) that means 2.034, there were tcount > ttable significantly different and Ha was accepted. The effect size was categorized as medium effect since the ES value was 0.7. In conclusions, student teams-achievement divisions is significant and effective for students' learning achievement in the thematic lesson to Year-4 students of Elementry School 03 Pontianak Selatan. Keywords: Effective, Students Teams-Achievement Divisions, Students’ Learning Achievemenet In The Thematic Lesson.